The Marketing Strategy of Palm Sugar “Gu Sereen Noniludo Group” in Lareh Sago Halaban District, Lima Puluh Kota Regency - Putri, Mega Amelia; Sonata, Sindi (Musamus University, 2022)
Gu Sereen is a brand of sugar products made from coconut water which is cooked into granules. Gu Sereen products were launched by Noniludo Group in September 2019. Gu Sereen products are still relatively new and not widely known to the public, requiring a strategy in marketing. Efforts to get the right marketing strategy obtained from the identification of internal and external factors. This study aims to describe and analyze the marketing strategy of Gu Sereen Noniludo Group. The study was carried out from April to May 2020. Determination of the sample was purposive. Data were analyzed using SWOT analysis. The main advantage of the product is a quality product without preservatives. Gu Sereen has a major market opportunity, namely consumers who prioritize a healthy lifestyle. The most appropriate strategy to be applied is the market penetration strategy by maximizing promotion and market expansion. The results of the SWOT analysis produce 10 alternative strategies that can be chosen by the company. An alternative strategy that is prioritized by the company is collaborating with minimarkets and herbal stores that are strategically located to be able to reach potential consumers with a TAS score of 6.486. Keywords: SWOT Analysis; Product; Market Penetration; Consumer